2015
DOI: 10.1109/tbme.2015.2444406
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preliminary Experimental Investigation of a Capsule for Measuring the Small Intestine Contraction Pressure

Abstract: A tethered pressure measurement capsule was developed for measuring the small intestine contraction pressure to assist in locating capsules within the gastrointestinal (GI) tract and quantifying the contact force between the capsule and the small intestine lumen. The capsule was calibrated statically and dynamically in depth-controlled water at body temperature (37-38 °C). In vitro tests were performed on an intestinal simulator to verify the measurement function of the capsule. To perform a preliminary evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, analytical modelling of frictional resistance between a capsule endoscope and the intestine was considered and validated by experiments [19][20][21]. Peristaltic motion of the small intestine can induce contraction pressure on the capsule robot, and a capsule of 12 mm in diameter and 30 mm in length with two pressure sensors was studied in [22] to measure such a pressure. In vitro tests by using a 72 kg live pig found that the contraction rate was 9.4-11 times per minute, and the peak contraction pressure was 0.24 ± 0.05 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analytical modelling of frictional resistance between a capsule endoscope and the intestine was considered and validated by experiments [19][20][21]. Peristaltic motion of the small intestine can induce contraction pressure on the capsule robot, and a capsule of 12 mm in diameter and 30 mm in length with two pressure sensors was studied in [22] to measure such a pressure. In vitro tests by using a 72 kg live pig found that the contraction rate was 9.4-11 times per minute, and the peak contraction pressure was 0.24 ± 0.05 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…The selflocalization features of the capsule are beyond the scope of this project, so to ensure the TAM deployed in the proper location, the ICR was implanted via enterotomy instead of via swallowing. According to a previous study, the difference in intestinal contact pressure on a solid bolus between a closed and an open abdomen is 0.28 kPa [17]. Thus, the ICR ejection performance under surgical implantation conditions (with an open abdomen) is likely similar to the performance of a capsule that is swallowed and activates in a closed abdominal pressure environment.…”
Section: In Vivo Animal Experimentmentioning
confidence: 83%
“…The keys to successful attachment are knowledge of capsule's location and intimate contact of the TAM with the tissue. The future sensor package will add these capabilities [17].…”
Section: Methodsmentioning
confidence: 99%
“…The coulomb friction comprises static and dynamic friction, as shown in Equations and , respectively. The peristaltic forces act in the form of waves and appear between 9.4 and 11 times per minute 27 . When the peristaltic force is absent, then the capsule would remain idle and static frictional force would resist the sampler movement as expressed in Equation .…”
Section: Methodsmentioning
confidence: 99%